Halogen emissions from a small volcanic eruption: Modeling the peak concentrations, dispersion, and volcanically induced ozone loss in the stratosphere - Millard, G; Mather, T; Pyle, D; Rose, W; Thornton, B (Geophysical Research Letters, 2016)
Aircraft measurements in the Hekla, Iceland volcanic plume in February 2000 revealed large quantities of hydrogen halides within the stratosphere correlated to volcanic SO2. Investigation of the longer-term stratospheric impact of these emissions, using the 3D chemical transport model, SLIMCAT suggests that volcanic enhancements of H2O and HNO 3 increased HNO3·3H2O particle availability within the plume. These particles activated volcanic HCl and HBr, enhancing model plume concentrations of ClOx (20 ppb) and BrO x (50 ppt). Model O3 concentrations decreased to near-zero in places, and plume average O3 remained 30% lower after two weeks. Reductions in the model O3 column reduced UV shielding by 15% for 2 days. Plume incorporation into the winter polar vortex after 1 March elevated model vortex Cly and Bry by 0.15 ppb and 7 ppt respectively, and doubled vortex ClOx and BrO. Model results agree quantitatively with the observations made by the DC-8 aircraft. Copyright 2006 by the American Geophysical Union.